La transition énergétique normande mise à l’épreuve par des profanes-néophytes - Frédéric Naudon (VertigO)
Can a lay person help a specialist – the “knowing” person – to better understand his own field ? Can he effectively participate in the creation of new knowledge alongside the specialist ? This article presents an original experimental device, proposing to laypersons-neophytes to test a technological project integrated in the ecological transition path that a French region, Normandy, has chosen for itself. New technical questions, unthought of social problems and astonishments on the way the project is conducted, laypersons-neophytes will push to favor the emergence of another path of energy transition and will make the difficulties appear, or perhaps the impossibility of mingling two different projects in a single final result – i.e. a hydrogen training boat and an industrial demonstrator. We hope the good results of this experimental device will keep the reflection going on the role of laypersons-neophytes in participatory devices and raise the question of their productive technical legitimacy.